Preliminary structural validation of the Afrikaans version of the Children's Hope Scale. Issue 2 (3rd March 2020) - Manuel, Donnay; Florence, Maria; Adams, Sabirah; Mpilo, Mulalo; Delport, Anton; Pienaar, Mariska; Sinclair, Deborah; Savahl, Shazly
Abstract : This study aimed to test the overall fit structure and reliability of scores from the Afrikaans version of the Children's Hope Scale. The validation sample comprised of 899 adolescent learners selected from 12 schools located in the Western Cape province of South Africa (female = 54%, male = 46%; age range = 13 to 16, M = 13.12, SD = 2.01). Confirmatory factor analysis yielded a unidimensional structure and acceptable fit indices and reliability of scores from the Afrikaans version of the Children's Hope Scale. Results support the use of the Afrikaans version of the Children's Hope Scale for research purposes.